Risk Factors for Construction Workforce Safety towards Sustainability - Asad, Muhammad Mujtaba; Sherwani, F.; Khand, Zahid Hussain (International Journal of Sustainable Construction Engineering and Technology, 2020)
This research article is based on the identification of safety risk factors associated with construction projects in Pakistan related with the China-Pakistan economic corridor (CPEC). In this paper, four construction sites have been targeted from Sindh, Punjab, Khyber Pakhtunkhwa, and Baluchistan province of Pakistan. The research was based on quantitative mode where the questionnaire survey was adopted for data collection and analysed statistically. The targeted respondents were 400 CPEC construction workforces from four different targeted sites in Pakistan. The collected data was analysed using descriptive statistical methods of Statistical Package of Social Sciences (SPSS) 23.0 software. According to the findings, it has been specified that the respondents from all four targeted construction sites in Pakistan has considered three major safety risk factors such as administrative, personal protective equipment (PPE) and workforce safety. Risk factors for administrative is between 1.06 and 2.65 (low level to moderate level), for PPE is between 1.06 and 2.65 (low level to moderate level) and for workforce safety is between 2.4 and 3.60 (moderate level to high Level). Meanwhile, the safety experts have been indicated the lack of proper training & PPE equipment’s, falling from height and falling object hazards are as the major cause of injuries at Pakistani construction sites related with CPEC projects. The findings of this study will be the catalyst for the CPEC projects in Pakistan to minimize the safety and health concern among construction industry workforce.